Methodology for in situ synchrotron X-ray studies in the laser-heated diamond anvil cell. Issue 2 (3rd April 2017) - Mezouar, M.; Giampaoli, R.; Garbarino, G.; Kantor, I.; Dewaele, A.; Weck, G.; Boccato, S.; Svitlyk, V.; Rosa, A. D.; Torchio, R.; Mathon, O.; Hignette, O.; et al.
ABSTRACT: A review of some important technical challenges related to in situ diamond anvil cell laser heating experimentation at synchrotron X-ray sources is presented. The problem of potential chemical reactions between the sample and the pressure medium or the carbon from the diamond anvils is illustrated in the case of elemental tantalum. Preliminary results of a comparison between reflective and refractive optics for high temperature measurements in the laser-heated diamond anvil cell are briefly discussed. Finally, the importance of the size and relative alignment of X-ray and laser beams for quantitative X-ray measurements is presented.